Comparison of The Right to Be Forgotten Regulations in Indonesia and European Union Countries - Kaendo, Karen Eklesia Gabriella; Adhari, Ade (Trunojoyo Madura University, 2025)
The development of digital technology has raised crucial issues related to personal data protection, one of which is related to the right to be forgotten. The European Union has strictly regulated this right through the General Data Protection Regulation (GDPR) since 2018, replacing the previous provisions in Directive 95/46/EC. The GDPR itself regulates the